Navigating Semi-colonialism : Shipping, Sovereignity, and Nation Building in China, 1860-1937 - Reinhardt, Anne; Reinhardt, Anne (Book collections on Project MUSE., 2018)
"Explores the development of the commercial shipping industry along the Yangzi River in the context of semi-colonialism and its impact on state and economy in late imperial and Republican China"--Provided by the publisher.